Images as Archival Material: Understanding the Circulation of Media Content About Europe (the Project Crossing Border Archives) - Matteo Treleani (VIEW Journal of European Television History and Culture)
In recent years, the question of the circulation of images has garnered interest from a variety of disciplinary and theoretical perspectives. This paper proposes a theoretical paradigm for analyzing the circulatory logics of audiovisual content, which serves as the foundation for the research project Crossing Border Archives (CROBORA). We advocate for the consideration of media images as archival material. The archival paradigm conceptualizes video sequences as components of larger units, enabling an understanding of how they are annotated, stored, and reused. CROBORA has collected and annotated 35,000 reuses of audiovisual archives from six French and Italian national newsreels from 2001 to 2020, focusing on themes related to the European Union. A case study examining the genealogy of the reuse of the video sequence of the Schuman Declaration will further elucidate this perspective.